Commensal E. coli Stx2 lysogens produce high levels of phages after spontaneous prophage induction - Iversen, Hildegunn; L' Abée-Lund, Trine M.; Aspholm, Marina; Arnesen, Lotte P. S.; Lindbäck, Toril (Frontiers in Cellular and Infection Microbiology, 2015)
Enterohemorrhagic E. coli (EHEC) is a food-borne pathogen that causes disease ranging from uncomplicated diarrhea to life-threatening hemolytic uremic syndrome (HUS) and nervous system complications. Shiga toxin 2 (Stx2) is the major virulence factor of EHEC and is critical for development of HUS. The genes encoding Stx2 are carried by lambdoid bacteriophages and the toxin production is tightly linked to the production of phages during lytic cycle. It has previously been suggested that commensal E. coli could amplify the production of Stx2-phages and contribute to the severity of disease. In this study we examined the susceptibility of commensal E. coli strains to the Stx2-converting phage ϕ734, isolated from a highly virulent EHEC O103:H25 (NIPH-11060424). Among 38 commensal E. coli strains from healthy children below five years, 15 were lysogenized by the ϕ734 phage, whereas lytic infection was not observed. Three of the commensal E. coli ϕ734 lysogens were tested for stability, and appeared stable and retained the phage for at least 10 cultural passages. When induced to enter lytic cycle by H2O2 treatment, 8 out of 13 commensal lysogens produced more ϕ734 phages than NIPH-11060424. Strikingly, five of them even spontaneously (non-induced) produced higher levels of phage than the H2O2 induced NIPH-11060424. An especially high frequency of HUS (60%) was seen among children infected by NIPH-11060424 during the outbreak in 2006. Based on our findings, a high Stx2 production by commensal E. coli lysogens cannot be ruled out as a contributor to the high frequency of HUS during this outbreak.